Two-photon polymerization based 4D printing of poly(N-isopropylacrylamide) hydrogel microarchitectures for reversible shape morphing - Ebrahim Yarali; Ayman Ahmed Mubeen; Kai Cussen; Lennart van Zanten; Vahid Moosabeiki; Amir A. Zadpoor; Angelo Accardo; Mohammad J. Mirzaali (Scientific Reports)
Abstract Incorporating shape-morphing capability into 3D microprinting enables the fabrication of 4D-printed microarchitectures as proof-of-concept actuators for potential use in soft robotics and microfluidic systems. The ability of these 3D microstructures to actuate rapidly and reversibly enables precise, non-invasive, and controllable deformation. In this study, we investigated the programmable shape-morphing behavior of 3D microarchitectures fabricated using two-photon polymerization (2PP) of a well-established temperature-responsive hydrogel, poly(N-isopropylacrylamide) (pNIPAM). We first systematically studied how 2PP 3D printing parameters (e.g., laser power, scanning speed) and the chemical composition of pNIPAM, including monomer and crosslinker, influence the shape morphing of bilayer microstructures within a temperature range of ~ 32 °C to 60 °C. The (thermo)mechanical properties of the hydrogels, including the Young’s modulus, thermal expansion coefficients, and angular deflection, were also measured at different laser doses and temperatures. Based on these experimental measurements, we calibrated a thermomechanical model capable of predicting the shape morphing of 4D-printed microarchitectures. These microarchitectures served as proof-of-concept actuators, demonstrating the potential of programmable microscale soft robotics and microfluidic systems. The findings provide design guidelines for engineering stimuli-responsive 3D microstructures, highlighting limitations and opportunities for future integration into functional soft robotic or microfluidic systems made of a single material.